PHOTOVOLTAIC ENERGY AS SUSTAINABLE ENERGETIC MATRIX IN COMPANIES (Revista Gestão & Sustentabilidade Ambiental, 2014)
The aim of this paper is investigate the evolution of the energetic photovoltaic matrix in the company NORD Eletric SA. This is justified by the importance of the sustainability and creation of clean energy making use of the emerging and innovative alternative in the regional area supporting the economic and environmental. The study used a qualitative and quantitative approach. The responsible for the company was interviewed and secondary data were researched. The techniques of analyze used were descriptive and content. The results show that it is possible and feasible the exploration of the photovoltaic energy strengthen and diversifying the energetic matrix characterized by local energy without transmission net. We realized that, from a management focused in new sustainable technologies it is possible to enlarge the Brazilian energetic matrix through alternative ways. Therefore, we conclude that the company looks for investment in technology applied to alternative energy to be competitive in business.